2016
DOI: 10.1371/journal.pone.0147579
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Private Medical Practitioners on Tuberculosis Notification: A Study from Chennai, South India

Abstract: BackgroundThe Government of India declared TB as a notifiable disease in 2012. There is a paucity of information on the government's mandatory TB notification order from the perspective of private medical practitioners (PPs).ObjectiveTo understand the awareness, perception and barriers on TB notification among PPs in Chennai, India.MethodsTotal of 190 PPs were approached in their clinics by trained field staff who collected data using a semi-structured and pre-coded questionnaire after getting informed consent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 8 publications
6
33
3
Order By: Relevance
“…11 This leads to delay diagnosis and spread on infection in community .Knowledge regarding RNTCP guidelines for case detection is likely to help in early diagnosis and cost reduction in TB management. 13 Similar reason was stated for referral by Hurtig et al in study conducted in Nepal. 10 Lack of affordability can lead discontinuation of treatment and lack of system for supervision of follow up among PPs can lead increased treatment default rate and emergence of drug resistance.…”
Section: Discussionsupporting
confidence: 63%
“…11 This leads to delay diagnosis and spread on infection in community .Knowledge regarding RNTCP guidelines for case detection is likely to help in early diagnosis and cost reduction in TB management. 13 Similar reason was stated for referral by Hurtig et al in study conducted in Nepal. 10 Lack of affordability can lead discontinuation of treatment and lack of system for supervision of follow up among PPs can lead increased treatment default rate and emergence of drug resistance.…”
Section: Discussionsupporting
confidence: 63%
“…Private sector participation in E-NIKSHAY is low but slowly gaining momentum [26,27]; our study therefore reflects a time period before a substantial increase in private sector notifications, when they had been historically very low. Only 38,596 TB patients were notified to the government by the private sector in 2013 [16], and, since treatment outcome data for these patients are not available, we exclude them from the cascade.…”
Section: Methodsmentioning
confidence: 99%
“…Raising awareness, collection of notification forms right at PP clinics and constant dialogue between RNTCP staff and PPs had no effect on notification in our study. Studies trying to understand the barriers to notification in India reported that not all PPs have fully understood the notification's rationale and that, although aware, many do not notify, the main reasons being lack of time, concerns regarding patients’ confidentiality and lack of trust in the government health system . Ensuring notification without legal backup seems difficult.…”
Section: Discussionmentioning
confidence: 99%